Proinflammatory and cardiovascular biomarkers are associated with echocardiographic abnormalities in children with HIV taking antiretroviral therapy. (1st December 2022) - Majonga, Edith D.; Yindom, Louis-Marie; Hameiri-Bowen, Dan; Mayini, Justin; Rehman, Andrea M.; Kaski, Juan P.; Mujuru, Hilda A.; Rowland-Jones, Sarah L.; Ferrand, Rashida A.
Abstract : Objectives: Children with perinatally acquired HIV (PHIV) and taking antiretroviral therapy (ART) have a high prevalence of subclinical cardiac disease. We hypothesized that cardiac disease may be a consequence of dysregulated systemic immune activation driven by HIV infection. We examined cardiovascular and proinflammatory biomarkers and their association with echocardiographic abnormalities in children with PHIV. Design: Cross-sectional analysis of soluble biomarkers from a prospective cohort of children aged 6–16 years with PHIV and age-matched HIV-uninfected comparison group. Methods: Cryopreserved plasma samples were used to measure seven soluble biomarkers using multiplex bead assay (Luminex). Multivariable logistic regression assessed how biomarker levels related to cardiac abnormalities. Results: A total of 406 children participated in this study (195 PHIV and 211 HIV-uninfected). Mean [standard deviation (SD)] ages of PHIV and HIV-uninfected participants were 10.7 (2.6) and 10.8 (2.8) years, respectively. Plasma levels of CRP, TNF-α, ST2, VCAM-1 and GDF-15 were significantly higher in the PHIV group compared with uninfected control ( P  < 0.001). Among children with PHIV, with one-unit representing one SD in biomarker level, a one-unit increase in CRP and GDF-15, was associated with increased odds of having left ventricular (LV) diastolic dysfunction [adjusted odds ratio (aOR), 1.49 (1.02–2.18; P  < 0.040)] and [aOR 1.71 (1.18–2.53; P  = 0.006)], respectively. Each one unit increase in GDF-15 was associated with increased odds of LV hypertrophy [aOR 1.84 (95% CI 1.10–3.10; P  < 0.021)]. Conclusion: Children with PHIV had higher levels of proinflammatory and cardiovascular biomarkers compared with HIV-uninfected children. Increased CRP and GDF-15 were associated with cardiac abnormalities in children with PHIV.